2017
DOI: 10.1016/j.matchemphys.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution and strengthening behavior in in-situ magnesium matrix composites fabricated by solidification processing

Abstract: In-situ magnesium matrix composites with three different matrix materials (including Mg, AZ91 and AE44 Mg-alloys) were fabricated by injecting cross-linked polymer directly into the molten Mg/Mg-alloys, and having it convert to the 2.5 vol% SiCNO ceramic phase using liquid stir-casting method. In-situ chemical reaction took place within the molten slurry tending to produce 42 and 18 vol% Mg 2 Si crystals in Mg and AE44 matrix composites, respectively but not in AZ91 matrix composite. Microstructural evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 31 publications
(18 reference statements)
1
18
0
Order By: Relevance
“…As in the previous case, the average diameter of the loop remains the same, with the prismatic loop coming near the surface of the sphere. Let A be the area of the averaged dislocation loop, which is pd 2 16 (the average loop diameter can be assumed as d/2), and q C be the total length of dislocation per unit volume. Ignoring the effect of the cooling rate,…”
Section: ½2mentioning
confidence: 99%
See 3 more Smart Citations
“…As in the previous case, the average diameter of the loop remains the same, with the prismatic loop coming near the surface of the sphere. Let A be the area of the averaged dislocation loop, which is pd 2 16 (the average loop diameter can be assumed as d/2), and q C be the total length of dislocation per unit volume. Ignoring the effect of the cooling rate,…”
Section: ½2mentioning
confidence: 99%
“…[17] Local yield strength is further estimated as 360.4 MPa using an empirical relation. [2,15,18,19] 3. Discussion The mechanical properties of MMCs depend on the size and distribution of reinforcements.…”
Section: ½2mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, combinations of the above strategies may be beneficial to achieve desired properties. Previous research has shown that designed magnesium matrix composites with refined grains can enhance both strength and ductility [ 8 , 9 , 10 ]. Among the various reinforcements, discontinuous ceramic nanoparticles have outstanding advantages such as chemical inertness, isotropic properties and excellent mechanical properties, which make them attractive for the preparation of magnesium matrix composites [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%